The study of uneven temperature field in billet electrodes during their graphitization in the castner furnace - Лелека, Сергій Володимирович; Лазарєв, Тарас Валерійович; Педченко, Анатолій Юрійович; Швачко, Денис Григорович (Eastern-European Journal of Enterprise Technologies, 2015)
We have experimentally studied the thermal and electric state of the Castner furnace, which allows adjusting and verifying the numerical data-based model. The analyzed physical experiment findings show that the billets which contact with a large volume of insulation material within a certain temperature range have a slightly reduced heating rate, which is probably due to the fact that some heat is spent on evaporation and further gasification of the carbon material. We have also found that the use of a ring-shaped inter-electrode gasket affects the temperature distribution in the fore part of the electrode billets since the shape of the gasket allows reducing the temperature difference along the axis of the central pieces. The obtained values of the water temperature spent on cooling of the electrical shunt allowed calculating an effective coefficient for the heat transfer from the surface of the graphite shunt to the cooling belt. The study has proved that the effective heat transfer coefficient has a constant value till the shunt surface temperature reaches the rate of 140 °C. If the temperature exceeds this level, the coefficient value grows because of the lower thermal contact resistance between the cooling belt and the graphite shunt due to the thermal expansion of the latter.